2013
DOI: 10.1063/1.4789902
|View full text |Cite
|
Sign up to set email alerts
|

Shape-anisotropic heterogeneous nucleation and magnetic Gibbs-Thomson effect in itinerant-electron metamagnetic transition of La(Fe0.88Si0.12)13 magnetocaloric compound

Abstract: Macroscopic anisotropy of spatial selectivity in magnetic nucleation and growth was clarified for itinerant-electron metamagnetic transition of La(Fe0.88Si0.12)13 by the time-dependent Ginzburg-Landau model combined with the Maxwell electromagnetic equation. Spontaneous generation of voltage supports symmetric growth in the longitudinal direction of the specimen as predicted by the simulation. The difference between nucleation-growth behaviors in thermally induced transition and those in field-induced transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…One possibility is strain relief: [ 5 ] in polycrystalline samples such as ours, where there is a period of mixed phase the growth itself is known to Adv. This would be consistent with Fujita et al [ 17 ] in which simulations and Seebeck voltage measurements of a rectangular sample suggest that the nucleation of the FM phase for the PM-FM transition occurs at the middle of the sample, whereas the FM-PM transition begins at the ends with respect to the applied fi eld direction. 2015, 5, 1401639 www.MaterialsViews.com www.advenergymat.de wileyonlinelibrary.com not be symmetric, [ 17 ] thus, one would expect any relief from breaking the sample to dominate for the PM-FM case only, where the material increases in volume.…”
Section: Using Sample Shape To Engineer the Magnetic Hysteresissupporting
confidence: 92%
See 1 more Smart Citation
“…One possibility is strain relief: [ 5 ] in polycrystalline samples such as ours, where there is a period of mixed phase the growth itself is known to Adv. This would be consistent with Fujita et al [ 17 ] in which simulations and Seebeck voltage measurements of a rectangular sample suggest that the nucleation of the FM phase for the PM-FM transition occurs at the middle of the sample, whereas the FM-PM transition begins at the ends with respect to the applied fi eld direction. 2015, 5, 1401639 www.MaterialsViews.com www.advenergymat.de wileyonlinelibrary.com not be symmetric, [ 17 ] thus, one would expect any relief from breaking the sample to dominate for the PM-FM case only, where the material increases in volume.…”
Section: Using Sample Shape To Engineer the Magnetic Hysteresissupporting
confidence: 92%
“…Here, we study the magnetization ( M ) dynamics of the transition in a fi rst-order metamagnetic material in response temperature in LaFe 13-x Si x -based materials; [13][14][15][16] generally the M-H loops show "fl aring" as the fi eld rate is increased resulting in increased magnetic hysteresis ( Figure 1 a). Alternatively in the latter case, it has also been suggested that this effect is an intrinsic nucleation and growth process dominated locally by heating/cooling at the phase boundary and the dipole interaction, [ 15,17 ] or by thermal activation over the energy barrier. In the former case once the PM-FM transition has started at some part of the sample, the increase in temperature from the nucleated region heats the surrounding regions and therefore increases their critical fi elds.…”
Section: Introductionmentioning
confidence: 99%
“…The transient for the lowest temperature shows, however, a peculiar clipping for low magnetic fields, which leads to the flat magnetic field dependence at low magnetic fields seen in Figure . Such an effect can be understood by the scenario schematically sketched in Figure : cooling of the paramagnetic La 1.2 Fe 11.4 Si 1.4 Mn 0.2 sample leads to thermally induced nucleation of the ferromagnetic phase (see Figure a) . Application of a modulated magnetic field leads then due to the MCE to temperature oscillations around the mean sample temperature (which equals the sample holder temperature) as the fraction of the ferromagnetic phase and hence the magnetization changes (see upper transient in Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…We have extracted the latent heat and the inverse heat capacity change in fragments taken from each sample and show that these also decrease to zero as T crit is approached, demonstrating the role played by local thermal linkage in the dynamics of the evolution of the transition. The local nature of the magnetic transition in these materials can be probed also with imaging techniques such as Hall probe imaging [14,25], and can be numerically simulated [26]. We have pointed out the important role of the thermal environment on the observed dynamics in these materials.…”
Section: Resultsmentioning
confidence: 99%